Separator and electrochemical device including same

The use of core-shell polymer particles with distinct glass transition temperatures and electrolyte-elutable polymers on the shell addresses adhesion issues in electrochemical devices, improving wet adhesion and long-term stability.

JP7612849B2Active Publication Date: 2025-01-14LG ENERGY SOLUTION LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023519542
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-10-20
Filing Date
2021-10-20
Publication Date
2025-01-14
Estimated Expiration
2041-10-20

AI Technical Summary

Technical Problem

Existing electrochemical devices face issues with adhesion to electrodes in electrolytic solutions, particularly with water-based binders, leading to interfacial peeling and reduced battery life due to insufficient adhesive strength, especially at low temperatures.

Method used

A separator with a porous polymer substrate coated by a binder polymer comprising core-shell type polymer particles, where the core and shell have different glass transition temperatures, and a polymer component is chemically bonded to the shell for elution in the electrolyte, enhancing entanglement and adhesion.

Benefits of technology

Improves wet adhesion and interfacial strength between the separator and electrode, maintaining long-term life characteristics and stability by controlling glass transition temperatures and preventing pore blockage, thus enhancing battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007612849000001
    Figure 0007612849000001
Patent Text Reader

Abstract

The separator includes a porous polymer substrate, and a porous coating layer located on at least one surface of the porous substrate, the porous coating layer including a plurality of inorganic particles and a binder polymer located on some or all of the surfaces of the inorganic particles and connecting and fixing the inorganic particles to each other, wherein the binder polymer includes core-shell polymer particles having a core and a shell surrounding the core, the core polymer contained in the core and the shell polymer contained in the shell have different glass transition temperatures, and a polymer of a component that is chemically bonded to the surface of the shell and is capable of eluting with an electrolyte is grafted thereto. An electrochemical device including the separator is also disclosed.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a separator and an electrochemical device including the same, and more particularly to a separator having improved adhesive strength with electrodes in an electrolyte and an electrochemical device including the same.

[0002] This application claims priority to Korean Patent Application No. 10-2020-0136313, filed on October 20, 2020, the entire contents of which are incorporated herein by reference in their entirety in the specification and drawings. [Background technology]

[0003] Recently, interest in energy storage technology has been increasing. As the fields of application expand to include energy for mobile phones, camcorders, and notebook PCs, as well as electric vehicles, efforts in the research and development of secondary batteries are gradually being made concrete. Secondary batteries are the field that has attracted the most attention from this perspective, and among them, the development of secondary batteries that can be charged and discharged is the focus of attention. Recently, in the development of such batteries, research and development on new electrode and battery designs is being advanced in order to improve capacity density and specific energy.

[0004] Among the secondary batteries currently in use, lithium secondary batteries, developed in the early 1990s, have been attracting attention due to their advantages of higher operating voltage and much higher energy density compared to conventional batteries that use aqueous electrolytes, such as Ni-MH, Ni-Cd, and sulfuric acid-lead batteries. However, such lithium ion batteries have the disadvantages of being complicated to manufacture and of having safety issues such as fire and explosion due to the use of organic electrolytes.

[0005] Recently, lithium-ion polymer batteries have been proposed as a next-generation battery that overcomes the drawbacks of lithium-ion batteries. However, the capacity of these batteries is still relatively low compared to lithium-ion batteries, and in particular, the discharge capacity at low temperatures is insufficient. Therefore, improvements in these areas are urgently needed.

[0006] Such electrochemical elements are produced by many manufacturers, but their safety characteristics are different from one another. It is very important to evaluate and ensure the safety of such electrochemical elements. The most important consideration is that the electrochemical element must not cause injury to the user when it malfunctions, and for this purpose, safety standards strictly regulate fire and smoke generation in the electrochemical element. In terms of the safety characteristics of electrochemical elements, if the electrochemical element overheats and goes into thermal runaway or the separator is penetrated, there is a high risk of explosion. In particular, polyolefin-based porous polymer substrates that are commonly used as separators for electrochemical elements exhibit severe thermal shrinkage behavior at temperatures above 100°C due to the material properties and the manufacturing process properties including stretching, causing a short circuit between the cathode and the anode.

[0007] In order to solve the safety problem of such electrochemical devices, a separator has been proposed in which a porous organic-inorganic coating layer is formed by coating at least one surface of a porous polymer substrate having a plurality of pores with a mixture of an excess amount of inorganic particles and a binder polymer.

[0008] The binder polymer used in the porous organic-inorganic coating layer is divided into oil-based binders and water-based binders depending on the type of dispersion medium of the composition for forming the coating layer. Conventionally, oil-based dispersion mediums and oil-based binders have been mainly used, but recently, interest in water-based dispersion mediums and water-based binders has been increasing due to issues such as environmental issues.

[0009] In this regard, one of the technical problems that water-based binders must solve in comparison with oil-based binders is ensuring wet adhesive strength and long-term adhesive strength.

[0010] Oil-based binders have a tendency to gradually increase adhesive strength over time as the binder molecules soak into the substrate, making it easier to maintain adhesive strength even if the electrode expands / contracts during cycling in a wet electrolyte state.

[0011] In contrast, water-based binders do not dissolve in electrolyte and have no entanglement effect, so there is little increase in adhesive strength over time. Therefore, water-based binders are likely to cause deterioration in battery life characteristics due to interfacial peeling due to insufficient adhesive strength when the electrode expands / contracts in an electrolyte-wet state or during cycling.

[0012] To address this issue, a method has been investigated in which an additive that dissolves from the electrolyte and exerts an entanglement effect is added to the composition for forming the porous coating layer; however, this additive may cause side effects such as blocking of the pores in the porous polymer substrate. Summary of the Invention [Problem to be solved by the invention]

[0013] An object of the present invention is to provide a separator having improved adhesive strength to electrodes in an electrolyte solution.

[0014] Another object of the present invention is to provide an electrochemical device including the separator. [Means for solving the problem]

[0015] In order to achieve the above object, according to one aspect of the present invention, a separator according to the following embodiment is provided.

[0016] According to the first embodiment, A porous polymer substrate; a porous coating layer located on at least one surface of the porous substrate, the porous coating layer including a plurality of inorganic particles and a binder polymer located on a part or all of the surface of the inorganic particles to connect and fix the inorganic particles to each other; the binder polymer includes core-shell type polymer particles having a core portion and a shell portion surrounding the core portion, the glass transition temperature of the core polymer contained in the core portion is different from that of the shell polymer contained in the shell portion; The separator is characterized in that a polymer having an electrolyte-dissolvable component that is chemically bonded to the surface of the shell is grafted thereon.

[0017] According to the second embodiment, in the first embodiment, The core polymer may have a higher glass transition temperature than the shell polymer.

[0018] According to the third embodiment, in the second embodiment, The core polymer may have a glass transition temperature of 85°C or higher, and the shell polymer may have a glass transition temperature of -100 to 20°C.

[0019] According to the fourth embodiment, in the second or third embodiment, The core polymer may include polystyrene, a polystyrene copolymer, polymethyl methacrylate, a polymethyl methacrylate copolymer, a polyamide-based polymer, or two or more of these, and the shell polymer may include an acrylate-based polymer, a rubber-based polymer, a urethane-based polymer, a silicone-based polymer, or two or more of these.

[0020] According to the fifth embodiment, in the first embodiment, The core polymer may have a lower glass transition temperature than the shell polymer.

[0021] According to the sixth embodiment, in the fifth embodiment, The core polymer may have a glass transition temperature of -100 to 20°C, and the shell polymer may have a glass transition temperature of 85°C or higher.

[0022] According to the seventh embodiment, in the fifth or sixth embodiment, The core polymer may include an acrylate-based polymer, a rubber-based polymer, a urethane-based polymer, a silicone-based polymer, or two or more of these, and the shell polymer may include a polystyrene-based polymer, a poly(meth)acrylate-based polymer, a polyamide-based polymer, or two or more of these.

[0023] According to the eighth embodiment, in any one of the first to seventh embodiments, The core-shell type polymer particles may be spherical with an average particle size of 100 nm to 1 μm.

[0024] According to the ninth embodiment, in any one of the first to eighth embodiments, The ratio of the average particle diameter of the core portion to the average particle diameter of the core-shell type polymer particles may be 50% to 90%.

[0025] According to a tenth embodiment, in any one of the first to ninth embodiments, The core-shell polymer particles may contain 100 parts by weight of a core portion and 10 to 300 parts by weight of a shell portion.

[0026] According to an eleventh embodiment, in any one of the first to tenth embodiments, The grafted polymer may include polyvinyl alcohol (PVA) or a copolymer thereof, polyethylene glycol (PEG) or a copolymer thereof, polypropylene glycol (PPG) or a copolymer thereof, polyvinyl acetate (PVAc) or a copolymer thereof, polyacrylonitrile (PAN) or a copolymer thereof, or two or more thereof.

[0027] According to the twelfth embodiment, in any one of the first to eleventh embodiments, The content of the grafted polymer may be 1 to 30 wt % based on the total weight of the core-shell type polymer particles.

[0028] According to a thirteenth embodiment, in any one of the first to twelfth embodiments, The core-shell type polymer particles may include core-shell type polymer particles having a shell polymer with a higher glass transition temperature than the core polymer; core-shell type polymer particles having a shell polymer with a lower glass transition temperature than the core polymer; or a combination of these core-shell type polymer particles.

[0029] According to the 14th embodiment, in any one of the 1st to 13th embodiments, The porous polymer substrate may be a polyolefin-based porous polymer substrate.

[0030] According to a fifteenth embodiment, there is provided an electrochemical device including a cathode, an anode, and a separator interposed between the cathode and the anode, wherein the separator is a separator according to any one of the first to fourteenth embodiments.

[0031] According to the 16th embodiment, in the 15th embodiment, The electrochemical device may be a lithium secondary battery. Effect of the Invention

[0032] According to one embodiment of the present invention, the binder polymer used in the porous coating layer of the separator includes core-shell type polymer particles having a core and a shell surrounding the core, and a polymer of an electrolyte-soluble component is grafted onto the surface of the shell through chemical bonding. The entanglement of the grafted chain with the electrolyte improves the wet adhesion and interface retention between the separator and the electrodes in the electrolyte, thereby improving the long-term life characteristics of an electrochemical device using such a separator.

[0033] In addition, by controlling the glass transition temperatures of the core polymer contained in the core part of the core-shell polymer particle and the shell polymer contained in the shell part to be different, when a soft polymer having a low glass transition temperature is used in the shell part and a hard polymer having a high glass transition temperature is used in the core part, the disadvantage of a water-based binder that the electrolyte solution has a reduced ability to penetrate into the binder polymer interface can be overcome, and the adhesive strength between the separator and the electrode in an electrolyte wet state can be significantly increased. Furthermore, when a hard polymer having a high glass transition temperature is used in the shell part and a soft polymer having a low glass transition temperature is used in the core part, excessive swelling of the soft polymer of the core part due to impregnation with the electrolyte solution can be suppressed, and the reduction or blocking of the pores of the porous coating layer due to the expansion of the core-shell polymer particles can be prevented, ensuring air permeability and eliminating the problem of increased resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0034] Hereinafter, a preferred embodiment of the present invention will be described in detail with reference to the attached drawings. Prior to this, the terms and words used in the specification and claims should not be interpreted as being limited to their ordinary or dictionary meanings, but should be interpreted as having meanings and concepts corresponding to the technical ideas of the present invention, in accordance with the principle that the inventor himself can appropriately define the concepts of terms in order to best describe the invention.

[0035] The separator according to one aspect of the present invention comprises a porous polymer substrate; a porous coating layer located on at least one surface of the porous substrate, the porous coating layer including a plurality of inorganic particles and a binder polymer located on a part or all of the surface of the inorganic particles to connect and fix the inorganic particles to each other; the binder polymer includes core-shell type polymer particles having a core portion and a shell portion surrounding the core portion, the glass transition temperature of the core polymer contained in the core portion is different from that of the shell polymer contained in the shell portion; The shell has a surface to which a polymer having an electrolyte-soluble component is grafted and chemically bonded thereto.

[0036] According to an embodiment of the present invention, the core polymer may have a higher glass transition temperature than the shell polymer.

[0037] In this case, the glass transition temperature of the core polymer may be 85° C. or higher, or 85 to 150° C., or 85 to 100° C. The glass transition temperature of the shell polymer may be −100 to 20° C., or −70 to 20° C., or −40 to 20° C.

[0038] Examples of the core polymer include polystyrene-based polymers, poly(meth)acrylate-based polymers, polyamide-based polymers, or two or more of these. Examples of the shell polymer include acrylate-based polymers, rubber-based polymers, urethane-based polymers, silicone polymers, or two or more of these.

[0039] More specifically, the poly(meth)acrylate polymer may include a homopolymer or copolymer of poly(meth)acrylate, a homopolymer or copolymer of polyalkyl(meth)acrylate, an alkyl acrylate-alkyl(meth)acrylate copolymer, a homopolymer or copolymer of polyfluoroalkyl(meth)acrylate, polyacrylonitrile, a homopolymer or copolymer of polyester, or two or more of these. Here, the alkyl may be, for example, a C1-C30 alkyl, a C1-C15 alkyl, a C1-C10 alkyl, or a C1-C5 alkyl.

[0040] For example, polymers such as polystyrene molecules are solid at room temperature, and as a result, such polymers are glassy and weak at room temperature. When observing a polystyrene polymer while increasing the temperature of the polymer, the molecular main chain, which is frozen at a certain temperature, starts Brownian motion (intramolecular motion caused by the rotation of bonds within the molecule, the entire molecule does not move so much that it changes its position), and as a result, the specific volume increases rapidly and the properties change to rubber-like. This change in state, i.e., from glassy to rubbery, is called glass transition, and the temperature at which this change in state occurs is called the glass transition temperature, T g (T stands for Temperature, and g stands for Glass). Polymer materials become harder or softer around this temperature, so T g is considered important in polymer properties. Also, the temperature at which Brownian motion begins, i.e., T g When using resin for machine parts, the conditions of use and T must be carefully considered. g Attention should be paid to the T g The difference is due to differences in the structure and composition of the polymer.

[0041] According to an embodiment of the present invention, the glass transition temperature may be measured using a DSC apparatus, such as a DSC (DSC823, METTLER TOLEDO) apparatus, a DSC (TA Instrument) apparatus, and the like.

[0042] In the core-shell type polymer particle having the core and the shell surrounding the core, g The shell part T g In other words, in order to improve the adhesive strength between the separator and the electrode, the T of the shell part located on the surface of the core-shell type polymer particle is larger than g Even if the core T g Since the morphology of the particles can be maintained due to the high solubility, the resistance of the separator does not increase, thereby minimizing the increase in resistance and increasing the electrode adhesion.

[0043] According to one embodiment of the present invention, the T g and T of the shell g The difference between the temperature and the temperature may be 10 to 200°C, 15 to 180°C, 20 to 160°C, or 20 to 80°C.

[0044] The ratio of the average particle diameter of the core portion to the average particle diameter of the core-shell type polymer particles may be 50% to 90%, or 60% to 90%, or 70% to 90%, or 80% to 90%, or 80% to 85%. When the ratio of the average particle diameter of the core portion to the average particle diameter of the core-shell type polymer particles satisfies such a range, the shape of the core portion is maintained and the adhesive strength of the shell portion is efficiently improved, thereby maintaining improved separator performance.

[0045] In the present invention, the average particle size of the core-shell type polymer particles, the average particle size of the inorganic particles, and the average particle size of the core portion are measured using a particle size measuring instrument (a laser particle size analyzer manufactured by Malvern Instruments). For example, the average particle size of the core portion may be measured after the core is synthesized, and the average particle size of the entire particles may be measured after the shell is synthesized.

[0046] The core-shell type polymer particles may include 100 parts by weight of the core part and 10 to 300 parts by weight, or 10 to 250 parts by weight, or 80 to 250 parts by weight, or 120 to 250 parts by weight, or 200 to 250 parts by weight, or 80 to 120 parts by weight of the shell part. When the weight ratio of the core part to the shell part satisfies such a range, the wet adhesive property is improved and the increase in the battery resistance due to the improvement in the air permeability can be controlled.

[0047] According to an embodiment of the present invention, the core polymer may have a lower glass transition temperature than the shell polymer, i.e., the shell polymer may have a higher glass transition temperature than the core polymer.

[0048] In this case, the glass transition temperature of the shell polymer may be 85° C. or higher, or 85 to 150° C., or 85 to 100° C. The glass transition temperature of the core polymer may be −100 to 20° C., or −70 to 20° C., or −40 to 20° C.

[0049] Examples of the shell polymer may include a polystyrene-based polymer, a poly(meth)acrylate-based polymer, a polyamide-based polymer, or two or more of these.

[0050] Examples of the core polymer may include an acrylate-based polymer, a rubber-based polymer, a urethane-based polymer, a silicone-based polymer, or two or more of these.

[0051] More specifically, the poly(meth)acrylate polymer may include a homopolymer or copolymer of poly(meth)acrylate, a homopolymer or copolymer of polyalkyl(meth)acrylate, an alkyl acrylate-alkyl(meth)acrylate copolymer, a homopolymer or copolymer of polyfluoroalkyl(meth)acrylate, polyacrylonitrile, a homopolymer or copolymer of polyester, or two or more of these. Here, the alkyl may be, for example, a C1-C30 alkyl, a C1-C15 alkyl, a C1-C10 alkyl, or a C1-C5 alkyl.

[0052] The ratio of the average particle diameter of the core portion to the average particle diameter of the core-shell type polymer particles may be 50% to 90%, or 60% to 90%, or 70% to 90%, or 80% to 90%, or 80% to 85%. When the ratio of the average particle diameter of the core portion to the average particle diameter of the core-shell type polymer particles satisfies such a range, the adhesive strength of the core portion is maintained, and the shell portion efficiently suppresses swelling of the core portion, thereby maintaining improved separator performance.

[0053] In the core-shell type polymer particle of the present invention, a polymer of an electrolyte-soluble component is present in a grafted form on the surface of the shell part, the polymer being chemically bonded to the surface of the shell part.

[0054] Here, the term "polymer having a component that can be dissolved in an electrolyte solution" refers to a polymer that has a chemical structure that has affinity with an electrolyte solution in at least one of the main chain and side chain of the polymer, and has the property that when mixed with an electrolyte solution, the polymer and the electrolyte solution do not undergo phase separation.

[0055] According to an embodiment of the present invention, the grafted polymer may include polyvinyl alcohol (PVA) or a copolymer thereof, polyethylene glycol (PEG) or a copolymer thereof, polypropylene glycol (PPG) or a copolymer thereof, polyvinyl acetate (PVAc) or a copolymer thereof, polyacrylonitrile (PAN) or a copolymer thereof, or two or more thereof.

[0056] The content of the grafted polymer may be 1 to 30 wt%, 1 to 25 wt%, or 1 to 20 wt% based on the total weight of the core-shell type polymer particles. When the content of the grafted polymer satisfies this range, the adhesive strength between the separator and the electrodes in the electrolyte is improved due to the entanglement phenomenon with the electrolyte, and the interface maintenance strength between the separator and the electrodes is improved, which significantly improves the long-term life characteristics of an electrochemical device using such a separator and contributes to cell stability.

[0057] According to an embodiment of the present invention, a method for grafting a polymer having an electrolyte-dissolvable component onto the surface of the shell of the core-shell type polymer particle may include the steps of: (1) mixing the core-shell type polymer particles dispersed in a solvent with an electrolyte-dissolvable polymer (e.g., a polymer having high crosslinking activity due to being treated with a coupling agent) dispersed in the solvent; (2) performing a sonification treatment; (3) removing unreacted materials by centrifugation; and (4) vacuum drying the remaining material.

[0058] The average particle size of the core-shell type polymer particles may be 100 nm to 1 μm, or 300 nm to 1 μm, or 300 nm to 800 nm. When the average particle size of the core-shell type polymer particles satisfies this range, it is advantageous in that the porous coating layer can be thinned and when inorganic particles are further included in the porous coating layer, it can be uniformly mixed with the inorganic particles.

[0059] According to an embodiment of the present invention, the core-shell type polymer particles may include: core-shell type polymer particles having a shell polymer having a higher glass transition temperature than the core polymer; core-shell type polymer particles having a shell polymer having a lower glass transition temperature than the core polymer; or a combination of these core-shell type polymer particles.

[0060] Specifically, as the core-shell type polymer particles, the particles in which the core polymer has a higher glass transition temperature than the shell polymer may be used alone, the particles in which the core polymer has a lower glass transition temperature than the shell polymer may be used alone, or the particles in which the core polymer has a higher glass transition temperature than the shell polymer and the particles in which the core polymer has a lower glass transition temperature than the shell polymer may be used together. When these two types of particles are used together, the weight ratio of the particles in which the core polymer has a higher glass transition temperature than the shell polymer and the particles in which the core polymer has a lower glass transition temperature than the shell polymer may be 9:1 to 1:9, or 7:3 to 3:7, or 7:3 to 5:5, or 5:5 to 7:3.

[0061] In the present invention, the average particle size D50 of the core-shell type polymer particles and inorganic particles described later can be defined as the particle size based on 50% of the particle size distribution. In the present invention, the average particle size D50 of the core-shell type polymer particles and inorganic particles can be measured, for example, by electron microscope observation using a scanning electron microscopy (SEM) or a field emission scanning electron microscopy (FE-SEM), or by a laser diffraction method. When measuring by the laser diffraction method, more specifically, the core-shell type polymer particles or inorganic particles are dispersed in a dispersion medium, then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT3000), and irradiated with ultrasonic waves of about 28 kHz at an output of 60 W, and the average particle size D50 based on 50% of the particle size distribution can be calculated in the measuring device.

[0062] Specifically, the porous polymer substrate may be a porous polymer film substrate or a porous polymer nonwoven fabric substrate.

[0063] The porous polymer film substrate may be a porous polymer film made of a polyolefin such as polyethylene or polypropylene, and such a polyolefin-based porous polymer film substrate exhibits a shutdown function at a temperature of, for example, 80 to 130°C.

[0064] In this case, the polyolefin-based porous polymer film may be formed by using a polyolefin-based polymer such as polyethylene (e.g., high density polyethylene, linear low density polyethylene, low density polyethylene, ultra-high molecular weight polyethylene), polypropylene, polybutylene, polypentene, etc., either alone or in combination of two or more of these.

[0065] In addition, the porous polymer film substrate may be manufactured by forming various polymers such as polyester in addition to polyolefin into a film shape. In addition, the porous polymer film substrate may be formed into a structure in which two or more film layers are laminated, and each film layer may be formed of the above-mentioned polymers such as polyolefin and polyester alone or a mixture of two or more of them.

[0066] In addition, the porous polymer film substrate and the porous nonwoven fabric substrate may be formed from a polymer such as polyethylene terephthalate, polybutylene terephthalate, polyester, polyacetal, polyamide, polycarbonate, polyimide, polyether ether ketone, polyether sulfone, polyphenylene oxide, polyphenylene sulfide, polyethylene naphthalene, etc., either alone or in combination, in addition to the polyolefin-based polymers described above.

[0067] The thickness of the porous polymer substrate is not particularly limited, but is preferably 1 to 100 μm, more preferably 5 to 50 μm. The pore size and porosity of the porous polymer substrate are not particularly limited, but are preferably 0.01 to 50 μm and 10 to 95%, respectively.

[0068] Non-limiting examples of inorganic particles contained in the porous coating layer include high dielectric constant inorganic particles having a dielectric constant of 5 or more, particularly 10 or more, inorganic particles having lithium ion transport ability, or a mixture thereof.

[0069] Non-limiting examples of inorganic particles having a dielectric constant of 5 or more include BaTiO3, Pb(Zr,Ti)O3 (PZT), Pb 1-x La x Zr 1-y Ti y O3(PLZT), P B (Mg 1 / 3 Nb 2 / 3 )O3-PbTiO3 (PMN-PT), hafnia (HfO2), SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, Y2O3, Al2O3, TiO2, SiC, AlO(OH), Al2O3·H2O, or mixtures thereof.

[0070] In the present specification, the term "inorganic particles having lithium ion transfer ability" refers to inorganic particles that contain lithium elements but do not store lithium and have the function of transferring lithium ions. Non-limiting examples of inorganic particles having lithium ion transfer ability include lithium phosphate (Li3PO4), lithium titanium phosphate (Li x Ti y (PO4)3, 0 <x<2、0<y<3)、リチウムアルミニウムチタンホスフェート(Li x Al y Ti z (PO4)3, 0 <x<2、0<y<1、0<z<3)、14Li2O-9Al2O3-38TiO2-39P2O5などのような(LiAlTiP) x O y Glass (0 <x<4、0<y<13)、リチウムランタンチタネート(Li x La y TiO3, 0 <x<2、0<y<3)、Li 3.25 Ge 0.25 P 0.75 Lithium germanium thiophosphate (Li x Ge y P z S w , 0 <x<4、0<y<1、0<z<1、0<w<5)、Li3Nなどのようなリチウムニトライド(Li x N y, (0 < x < 4, 0 < y < 2), SiS2-based glasses such as Li3PO4-Li2S-SiS2 (Li x Si y S z , (0 < x < 3, 0 < y < 2, 0 < z < 4), P2S5-based glasses such as LiI-Li2S-P2S5 (Li x P y S z , (0 < x < 3, 0 < y < 3, 0 < z < 7), or mixtures thereof, etc.

[0071] Further, the ratio of the average particle size of the core-shell type polymer particles to the average particle size of the inorganic particles is 80% to 200%, and according to one embodiment of the present invention, it can be 80% to 190%, or 84% to 188%. When the ratio of the average particle size of the core-shell type polymer particles to the average particle size of the inorganic particles is 80% to 200%, the core-shell type polymer particles can be distributed on the surface of the separator, and an advantageous effect of adhesion between the electrode and the separator is exhibited.

[0072] The thickness of the porous coating layer is not particularly limited, but specifically, it is 1 to 10 μm, more specifically, 1.5 to 6 μm. The porosity of the porous coating layer is also not particularly limited, but it is preferably 35% to 65%.

[0073] The weight ratio of the core-shell type polymer particles to the inorganic particles can be 5:95 to 80:20, or 20:80 to 80:20, or 50:50 to 80:20. When the weight ratio satisfies such a range, the heat resistance characteristics of the porous coating layer can be ensured, and the battery stability can be improved by the core-shell type polymer particles.

[0074] The separator according to one aspect of the present invention may further contain other additives as components of the porous coating layer.

[0075] According to an embodiment of the present invention, the porous coating layer may be a water-based coating layer using a water-based slurry. In the case of a water-based coating layer, it is advantageous for thin film coating and may be more advantageous in terms of reducing the resistance of the separator.

[0076] A method for manufacturing a separator according to an embodiment of the present invention is as follows.

[0077] In order to form the porous coating layer, inorganic particles and core-shell type polymer particles may be added to an aqueous dispersion medium and dispersed therein to prepare a composition for forming the porous coating layer. The inorganic particles may be added in a state in which they have been crushed to have a predetermined average particle size, or the inorganic particles may be added to the core-shell type polymer particles, and then crushed and dispersed while controlling the amount of the inorganic particles to have a predetermined average particle size using a ball mill method or the like.

[0078] The core-shell polymer particles can be prepared by various known methods such as emulsion polymerization, suspension polymerization, massive polymerization, solution polymerization, or bulk polymerization, and in one example, they can be prepared by emulsion polymerization.

[0079] The method of coating the porous polymer substrate with the composition for forming the porous coating layer is not particularly limited, but it is preferable to use a slot coating or dip coating method. Slot coating is a method in which a composition supplied through a slot die is applied to the surface of a substrate, and the thickness of the coating layer can be adjusted depending on the flow rate supplied from a metering pump. Dip coating is a method in which a substrate is immersed in a tank filled with a composition to coat it, and the thickness of the coating layer can be adjusted depending on the concentration of the composition and the speed at which the substrate is removed from the composition tank, and after immersion, it can be post-weighed with a Mayer bar or the like for more accurate control of the coating thickness.

[0080] The porous polymer substrate coated with the composition for forming a porous coating layer is dried using a dryer such as an oven, thereby forming a porous coating layer on at least one surface of the porous polymer substrate.

[0081] After the composition for forming the porous coating layer is coated on the porous polymer substrate, the dispersion medium may be removed by drying at 90 to 180° C., more specifically, at 100 to 150° C.

[0082] In a specific embodiment of the present invention, the core-shell type polymer particles of the porous coating layer can attach the inorganic particles to each other (i.e., connect and fix the inorganic particles to each other) so that the inorganic particles can maintain a state of being bound to each other, and the core-shell type polymer particles can maintain a state of being bound to the inorganic particles and the porous polymer substrate. The inorganic particles and the core-shell type polymer particles of the porous coating layer can form an interstitial volume in a state of being substantially in contact with each other. In this case, the interstitial volume means a space limited by the inorganic particles and the core-shell type polymer particles that are substantially in contact with each other in a packed structure (closed packed or densely packed) of the inorganic particles and the core-shell type polymer particles. The interstitial volume between the inorganic particles and the core-shell type polymer particles can become an empty space and form pores of the porous coating layer. In this case, the polymer contained in the shell portion of the core-shell type polymer particles acts as a binder polymer during the drying process, connecting and fixing the shell portions of the core-shell type polymer particles to each other, and connecting the porous polymer substrate and the core-shell type polymer particles to each other, thereby forming a porous coating layer.

[0083] Non-limiting examples of the dispersion medium used in this case include water alone or a mixture of water and one compound selected from the group consisting of methanol, ethanol, isopropyl alcohol, propanol, and water.

[0084] An electrochemical device according to one aspect of the present invention includes a cathode, an anode, and a separator interposed between the cathode and the anode, the separator being the separator according to one embodiment of the present invention described above.

[0085] Such electrochemical devices include all devices that perform electrochemical reactions, and specifically include all kinds of primary batteries, secondary batteries, fuel cells, solar cells, and capacitors such as supercapacitor devices, etc. Among the secondary batteries, lithium secondary batteries, including lithium metal secondary batteries, lithium ion secondary batteries, lithium polymer secondary batteries, and lithium ion polymer secondary batteries, are particularly preferred.

[0086] The cathode and anode electrodes to be used with the separator of the present invention are not particularly limited, and may be prepared by bonding an electrode active material to an electrode current collector by a conventional method known in the art. Among the electrode active materials, non-limiting examples of the cathode active material include conventional cathode active materials used in the cathode of conventional electrochemical devices, and in particular, lithium manganese oxide, lithium cobalt oxide, lithium nickel oxide, lithium iron oxide, or a lithium composite oxide obtained by combining these materials. Non-limiting examples of the anode active material include conventional anode active materials used in the anode of conventional electrochemical devices, and in particular, lithium adsorbent materials such as lithium metal or lithium alloy, carbon, petroleum coke, activated carbon, graphite, or other carbons are preferred. Non-limiting examples of the cathode current collector include foils made of aluminum, nickel, or a combination thereof, and non-limiting examples of the anode current collector include foils made of copper, gold, nickel, or a copper alloy, or a combination thereof.

[0087] The electrolyte that can be used in the electrochemical element of the present invention is + B - A salt having the structure: + Li + , Na + , K + or a combination thereof, such as B - PF6 - , BF4 - , Cl- , Br - , I - , ClO4 - , AsF6 - , CH3CO2 - , CF3SO3 - , N(CF3SO2)2 - , C(CF2SO2)3 - Examples of the salts containing anions such as those listed above or ions consisting of a combination thereof are dissolved or dissociated in an organic solvent consisting of propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, tetrahydrofuran, N-methyl-2-pyrrolidone (NMP), ethyl methyl carbonate (EMC), γ-butyrolactone, or a mixture thereof, but are not limited thereto.

[0088] The electrolyte injection can be performed at a suitable stage in the battery manufacturing process depending on the manufacturing process and the required properties of the final product, i.e., before the assembly of the battery or at the final stage of the battery assembly.

[0089] The present invention will be described below with reference to specific examples. However, the examples according to the present invention can be modified into many other forms, and the scope of the present invention should not be construed as being limited to the following examples. The examples of the present invention are provided to more completely explain the present invention to those having ordinary skill in the art.

[0090] Example 1 Alumina (Al2O3) with an average particle size D50 of 500 nm and core-shell type polymer particles (CSG1) with a polymer of electrolyte-soluble components chemically bonded to the shell surface were mixed with water in a weight ratio of 8:2, and the mixture was dispersed with beads for 2 hours using a paint shaker to prepare a slurry for the porous coating layer. At this time, the core of the core-shell type polymer particles was made of polystyrene (T g : 100℃), and the shell is made of polyurethane (T g : -30°C), and the grafted polymer was polyvinyl alcohol. The content of the grafted polymer was 10 wt% based on the total weight of the core-shell type polymer particles. The average particle size D50 of the core-shell type polymer particles was 300 nm. The ratio of the average particle size of the core part to the average particle size of the core-shell type polymer particles was 80%.

[0091] The slurry thus prepared was coated on both sides of a polyethylene porous film (thickness 12 μm) by dip coating and dried at a temperature of 85° C. for 2 hours to prepare a separator (total thickness 15 μm) having a porous coating layer (thickness 1.5 μm) on each side.

[0092] Example 2 Alumina (Al2O3) with an average particle size D50 of 500 nm and core-shell type polymer particles (CSG2) with a polymer of electrolyte-soluble components grafted to the shell surface by chemical bonding were mixed in water at a weight ratio of 8:2, and the mixture was dispersed with beads using a paint shaker for 2 hours to prepare a slurry for the porous coating layer. At this time, the core of the core-shell type polymer particles was polyurethane (T g : -30℃) and the shell is made of polystyrene (T g: 100°C), and the grafted polymer was polyvinyl alcohol. The content of the grafted polymer was 10 wt% based on the total weight of the core-shell type polymer particles. The average particle size D50 of the core-shell type polymer particles was 300 nm. The ratio of the average particle size of the core part to the average particle size of the core-shell type polymer particles was 80%.

[0093] The slurry thus prepared was coated on both sides of a polyethylene porous film (thickness 12 μm) by dip coating and dried at a temperature of 85° C. for 2 hours to prepare a separator (total thickness 15 μm) having a porous coating layer (thickness 1.5 μm) on each side.

[0094] Example 3 Alumina (Al2O3) having an average particle size (D50) of 500 nm, the core-shell type polymer particles (CSG1) having a polymer grafted to the surface of the shell used in Example 1, and the core-shell type polymer particles (CSG2) having a polymer grafted to the surface of the shell used in Example 2 were mixed in water at a weight ratio of 8:1:1, and the mixture was dispersed together with beads using a paint shaker for 2 hours to prepare a slurry for the porous coating layer.

[0095] The slurry thus prepared was coated on both sides of a polyethylene porous film (thickness 12 μm) by dip coating and dried at a temperature of 85° C. for 2 hours to prepare a separator (total thickness 15 μm) having a porous coating layer (thickness 1.5 μm) on each side.

[0096] Comparative Example 1 Alumina (Al2O3) with an average particle size (D50) of 500 nm and polyurethane (T g A separator was manufactured in the same manner as in Example 1, except that the porous coating layer slurry was prepared by dispersing the mixture together with beads in a paint shaker for 2 hours.

[0097] Comparative Example 2 A separator was prepared in the same manner as in Example 1, except that a slurry for a porous coating layer was prepared using core-shell type polymer particles in which a polymer having an electrolyte-dissolvable component that was not grafted to the shell surface by chemical bonding was not used.

[0098] In this case, the core of the core-shell type polymer particle is made of polystyrene (T g : 100℃), and the shell is made of polyurethane (T g : -30℃).

[0099] Comparative Example 3 A separator was prepared in the same manner as in Example 2, except that a slurry for a porous coating layer was prepared using core-shell type polymer particles in which a polymer having an electrolyte-dissolvable component that was not grafted to the shell surface by chemical bonding was not used.

[0100] In this case, the core of the core-shell type polymer particle is polyurethane (T g : -30℃) and the shell is made of polystyrene (T g : 100℃).

[0101] Evaluation method and results How to measure glass transition temperature The glass transition temperatures T g was measured using a DSC (DSC823, METTLER TOLEDO) instrument.

[0102] Average particle size (D50) The core-shell polymer particles or inorganic particles of Examples 1 to 3 and Comparative Examples 1 to 3 were dispersed in a dispersion medium, and then introduced into a commercially available laser diffraction particle size measuring device (Microtrac MT3000) and irradiated with ultrasonic waves of about 28 kHz at an output of 60 W, and the average particle size D50 at the 50% standard of the particle size distribution was calculated in the measuring device. The average particle size of the core part of the core-shell polymer particles was calculated by the same method as above for the core part particles before the shell part was formed.

[0103] Breathability (Gurley) The air permeability of the separators produced in Examples 1 to 3 and Comparative Examples 1 to 3 was measured according to the ASTM D726-94 method, and the results are shown in Table 1. Gurley, as used herein, is the resistance to air flow and was measured using a Gurley densometer. The air permeability values ​​described herein were measured by passing 1 in of the separators produced in Examples 1 to 3 and Comparative Examples 1 to 3 through 100 cc of air under a pressure of 12.2 inH2O. 2 The time required for the air to pass through the cross section of the sample was expressed as the aeration time (seconds).

[0104] Electrical Resistance (ER) The separators manufactured in Examples 1 to 3 and Comparative Examples 1 to 3 were immersed in an electrolyte (ethylene carbonate (EC):diethyl carbonate (DEC)=3:7, LiPF61.0M) and then the AC resistance was measured, and the results are shown in Table 1. The AC resistance was measured at 1 KHz using a Hioki device.

[0105] Electrode adhesion strength under electrolyte impregnation conditions -Measuring device: UTM (LLOYD INSTRUMENT LS 1) - Sample preparation and measurement method The lithium cobalt composite oxide:conductive material (Denka black):binder (PVdF) were weighed out to a weight ratio of 95:2.5:2.5, and then mixed in N-methylpyrrolidone (NMP) to prepare a positive electrode mixture. The positive electrode mixture was coated on an aluminum foil having a thickness of 20 μm to a thickness of 200 μm, and then rolled and dried to prepare a positive electrode.

[0106] As the electrolyte, a carbonate-based electrolyte was prepared by dissolving 1 mole of LiPF6 in a mixed solution of ethyl carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 1:1.

[0107] Then, 1) the produced positive electrode and separator were cut (20 x 60 mm), 2) the cut positive electrode and separator were interposed and inserted into an aluminum (Al) pouch, at which point the aluminum pouch was cut to 200 x 80 mm and then folded to 100 x 80 mm and the sides were sealed. 3) 1 g of the produced electrolyte was poured into the pouch and vacuum sealed. 4) The sealed pouch battery was pre-aged for one day. 5) Using a jig to hold the pre-aged pouch battery, the pre-aged pouch battery was heated to 60°C and 5 kgf / cm. 2 4) The specimen was heated and pressurized for 10 minutes at 40°C for 10 minutes, 5) the heated and pressurized pouch battery was opened to take out the wet bonded positive electrode and separator, 6) the pouch battery was opened to take out the wet bonded positive electrode and separator, 7) once taken out, the specimen was fixed to a glass plate using double-sided tape, with the positive electrode facing the glass slide, 8) the separator portion of the specimen was peeled off at an angle of 90° at a speed of 200 mm / sec at 25°C, and the strength at this time was measured as the adhesive strength between the positive electrode and the separator (the average value of 30-70% of the adhesive strength measurement area was measured, excluding the measurement start and end points).

[0108] Battery life characteristics <Secondary battery manufacturing> The lithium cobalt composite oxide:conductive material (Denka black):binder (PVdF) were weighed out to a weight ratio of 95:2.5:2.5, and then mixed in N-methylpyrrolidone (NMP) to prepare a positive electrode mixture. The positive electrode mixture was coated on an aluminum foil having a thickness of 20 μm to a thickness of 200 μm, and then rolled and dried to prepare a positive electrode.

[0109] The negative electrode was made of Li metal, and the electrolyte was a carbonate-based electrolyte in which 1 mole of LiPF6 was dissolved in a mixed solution of ethyl carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 1:1.

[0110] The separators prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were placed between the positive electrode and the negative electrode and placed in a pouch case, and the electrolyte was injected and sealed to prepare lithium secondary batteries.

[0111] <Measurement method> The lithium secondary battery thus manufactured was charged and discharged once at 0.1C in a voltage range of 3.0V to 4.4V in a chamber at 25°C, and then charged and discharged at 1.0C and 1.0C, and the life characteristics were measured 300 times. At this time, the life characteristics were expressed as a capacity retention rate calculated by the ratio of the discharge capacity after 300 cycles to the first discharge capacity. The results are shown in Table 1 below.

[0112] [Table 1]

[0113] Referring to Table 1, when the separators of Examples 1 to 3 using core-shell type polymer particles having a core and shell with different glass transition temperatures and a polymer grafted onto the surface of the shell as the binder polymer were used, the life characteristics of the secondary battery and the adhesive strength with the electrode (cathode) under electrolyte impregnation conditions were both significantly improved compared to the separators of Comparative Examples 1 to 3.

Claims

1. A porous polymer substrate; a porous coating layer located on at least one surface of the porous polymer substrate, the porous coating layer including a plurality of inorganic particles and a binder polymer located on a part or all of the surface of the inorganic particles to connect and fix the inorganic particles to each other; the binder polymer includes core-shell type polymer particles having a core portion and a shell portion surrounding the core portion, the glass transition temperature of the core polymer contained in the core portion is different from that of the shell polymer contained in the shell portion; a polymer having a component that can be dissolved in an electrolyte and is chemically bonded to a surface of the shell portion is grafted; The separator according to claim 1, wherein the content of the grafted polymer is 1 to 30% by weight based on the total weight of the core-shell type polymer particles.

2. The separator according to claim 1 , wherein the core polymer has a higher glass transition temperature than the shell polymer.

3. 3. The separator according to claim 2, wherein the core polymer has a glass transition temperature of 85°C or higher, and the shell polymer has a glass transition temperature of -100 to 20°C.

4. 4. The separator according to claim 2 or 3, wherein the core polymer comprises polystyrene, a polystyrene copolymer, polymethyl methacrylate, a polymethyl methacrylate copolymer, a polyamide-based polymer, or two or more of these, and the shell polymer comprises an acrylate-based polymer, a rubber-based polymer, a urethane-based polymer, a silicone-based polymer, or two or more of these.

5. The separator according to claim 1 , wherein the core polymer has a lower glass transition temperature than the shell polymer.

6. 6. The separator according to claim 5, wherein the core polymer has a glass transition temperature of -100 to 20°C, and the shell polymer has a glass transition temperature of 85°C or higher.

7. 7. The separator according to claim 5, wherein the core polymer comprises an acrylate-based polymer, a rubber-based polymer, a urethane-based polymer, a silicone-based polymer, or two or more of these, and the shell polymer comprises a polystyrene-based polymer, a poly(meth)acrylate-based polymer, a polyamide-based polymer, or two or more of these.

8. 8. The separator according to claim 1, wherein the core-shell type polymer particles are spherical and have an average particle size of 100 nm to 1 μm.

9. 9. The separator according to claim 1, wherein a ratio of an average particle size of the core portion to an average particle size of the core-shell type polymer particles is 50% to 90%.

10. 10. The separator according to claim 1, wherein the core-shell polymer particles contain 100 parts by weight of a core portion and 10 to 300 parts by weight of a shell portion.

11. The separator according to any one of claims 1 to 10, characterized in that the grafted polymer comprises polyvinyl alcohol (PVA) or a copolymer thereof, polyethylene glycol (PEG) or a copolymer thereof, polypropylene glycol (PPG) or a copolymer thereof, polyvinyl acetate (PVAc) or a copolymer thereof, polyacrylonitrile (PAN) or a copolymer thereof, or two or more of these.

12. 2. The separator according to claim 1, wherein the core-shell type polymer particles include: a core-shell type polymer particle having a shell polymer having a higher glass transition temperature than the core polymer; a core-shell type polymer particle having a shell polymer having a lower glass transition temperature than the core polymer; or a combination of these core-shell type polymer particles.

13. The separator according to claim 1 , wherein the porous polymer substrate is a polyolefin-based porous polymer substrate.

14. An electrochemical device comprising a cathode, an anode, and a separator interposed between the cathode and the anode, An electrochemical element, characterized in that the separator is the separator according to any one of claims 1 to 13.

15. 15. The electrochemical device according to claim 14, which is a lithium secondary battery.

Citation Information

Patent Citations

  • separator

    JP2012111205A

  • Separator for rechargeable battery and rechargeable lithium battery including the same

    KR1020180003177A

  • Separator and electrochemical device containing the same

    KR1020200050439A

  • An adhesive separator and a method for manufacturing the same

    KR1020200061576A

  • Adhesive for lithium ion secondary batteries, separator for lithium ion secondary batteries, and lithium ion secondary battery

    WO2015005145A1